AB0424 Retrospective Evaluation of Mycophenolate Mofetil Infectious Side Effects on Lupus Nephritis Patients. (15th July 2016) - Meirinhos, T.; Mariz, E.; Castro Ferreira, I.; Neto, R.; Pereira, E.; Costa, L.
Abstract : Background: Systemic lupus erythematosus (SLE) is a multifaceted autoimmune disease driven by auto-reactive immune cells, in particular B cells that target multiple organ systems leading to severe complications. A main complication of SLE is nephritis, formally known as lupus nephritis (LN). MMF is a selective, non-competitive and reversible inhibitor of inosine monophosphate dehydrogenase. MMF provided to be useful in the treatment of patients affected by SLE, especially in those with LN. MMF demonstrated a more favorable safety profile compared with cyclophosphamide, especially in terms of alopecia and infertility rates. Nonetheless, the use of MMF in LN has not been extensively evaluated in terms of safety and infection rates. Objectives: To study the prevalence of infections complications in a cohort of adult LN patients under MMF maintenance therapy. Methods: Retrospective study, enrolling patients attending a Rheumatology/Nephrology department, diagnosed with SLE (American College of Rheumatology criteria) and LN, under MMF maintenance therapy. Drug variables: dose of MMF, time of exposure. Clinical variables: age, gender, race, disease duration, histological classification (renal biopsy), specific organ involvement, other therapeutics for SLE, serum urea and creatinine, 24h proteinuria, and urinary sediment. Statistical analysis with Microsoft Excel 2010; appropriate statistical tests were used; p value<0.05 with a 95% confidence interval will be assumed. Results: 44 SLE patients were enrolled, 37 were female (84.1%); mean age was 38.4±11.9 years and mean disease duration was 122.9±108 months. All the patients were white. 35 patients (80%) had class 4 LN, 5 had class 5 and histological classification was unknown in 4 patients. 34 (77%) patients had extra renal disease, 23 with joint disease and 14 with cutaneous involvement. Mean MMF dose was 1018±876mg. 35 (79%) patients were doing steroid therapy, mean dose 5.58±3.87mg and 39 (88.6%) patients under Hidroxicloroquine therapy. We identify 25 infectious events, 4 (16%) needing hospitalization, none death. Mean time to infection after MMF introduction was 12.16±16.3 months. The most frequent infections include urinary tract infections (UTI) (8 patients), cutaneous Herpes Zoster (4 patients) and respiratory tract infections (4 patients). We found a positive correlation between the occurrence of infection in the first 8 months of therapy and 24h Proteinúria and dsDNA in the beginning of therapy (p=0.04 and p=0.03, respectively). Hidroxicloroquine seem to have a protective effect against infections, but no statistic association was found. We found no association between infections and MMF/steroid dose or renal function. Conclusions: We found significant morbidity associated with an increase incidence of infection after introduction of MMF, especially in the first months of therapy and patients with more active disease in the beginning of MMF. No mortality was associated with these infectious complications, and the hospital admission rate was low. References: Afzali B, Shah S, Chowdhury P, et al. Low-dose mycophenolate mofetil is an effective and safe treatment to permit phased reduction in calcineurin inhibitors in chronic allograft nephropathy. Transplantation 2005; 79: 304–309. Disclosure of Interest: None declared